Legal and Cultural Foundations for Improving Criminal Liability for Wartime Collaboration in Ukraine - Knyzhenko, Oksana; Knyzhenko, Svitlana; Krainyk, Hryhorii; Sharandak, Andrii; Svintsytskyi, Andrii (Udayana Journal of Law and Culture; Vol 9 No 2 (2025)DO - 10.24843/UJLC.2025.v09.i02.p05, 2025)
Following Russia’s full-scale invasion of Ukrainian territories, there have been significant changes in Ukrainian criminal legislation, particularly regarding the liability of individuals for collaboration with the aggressor country. Prior to 2022, the law included provisions specifically addressing treason, which encompassed three forms of criminal behavior: defecting to the enemy during wartime, espionage, and aiding foreign entities in subversive activities against Ukraine. New provisions have been introduced to establish liability for wartime collaboration in addition to treason; however, these provisions lack legal clarity and precision. This study analyzes relevant court decisions under Article 111-1 of the Criminal Code of Ukraine to identify patterns in judicial practice and assess both the effectiveness and shortcomings of the current legal framework. Beyond the legal aspects, the paper also examines the cultural dimension of collaboration, focusing on the preservation of cultural heritage amid occupation and information warfare. This research aims to develop scientifically grounded principles for legislators to consider when amending the provisions related to criminal liability for wartime collaboration. The methodology of this research employs historical, comparative-legal, logical, and system-structural methods. This paper proposes the establishment of a special commission tasked with refining criminal law to address the complex nature of liability for wartime collaboration. The outcomes of this commission’s work should produce well-founded legal norms that are economically, politically, and socially balanced, clearly defining the forms of criminally punishable wartime collaboration and establishing appropriate sanctions.